THE FUNCTIONS OF METAPHOR IN THE LYRICS OF RAYOLA’S SONG - SN, Nasrul (International Journal of Humanity Studies (IJHS), 2018)
This study aims to show some of the functions of the metaphor used in the lyrics of Rayola’s song. Rayola is a singer of Minang’s songs from Padang. The method used in this research is qualitative research in three stages: stage the provision of data, data analysis, and presentation of the results of the data analysis. Sources of data in the form of a song sung by Rayola, consisting of 8 albums Rayola ever published and commercialized. The theory used in this research is the theory of metaphor which is initiatived by Lakoff and Johnson (1980) as well as the theory of metaphor functions according to Stefanowitsch (2005). The results of this study revealed that there are at least seven functions of  metaphor contained in the lyrics of Rayola’s song 1) to concrete  human experience, 2) creating space imagination, 3) soften the language, 4) means to achieve aesthetic effects, 5) to attract attention, 6) to beautify the tone, and 7) pleasing to be heard.DOI: https://doi.org/10.24071/ijhs.2018.020107